Virtual Roaming Data Services and Seamless Technology Change: GSM, LTE, WiFi, Satellite, CDMA - Henry-Labordère, Arnaud (River Publishers Series in Communications, 2022)
The subject is "Virtual Roaming for data services" and "Seamless Technology change" also called "Number Continuity"."Virtual Roaming for voice and SMS" was covered in one of the author's previous book. "Virtual Roaming" means that it allows a subscriber to visit a network which his home network does not have an agreement with. The "Seamless Technology change" allows a user to keep all his services including reception of calls and SMS sent to his usual number when he switches his GSM to a Satellite phone or to WiFi. The implementation of Seamless Technology change uses the SS7 Roaming Hub and GTP Hubs technology explained in the first part of the book. The book also contains chapters explaining in detail the steering and anti-steering of roaming, LTE Serving Mobile Location Centers, and Advanced Policy and Charging implementations in LTE and 3G. This is to be used as an easy reference book. All the relevant references to the standards are included chapter by chapter. This is the first book on the two main subjects of Virtual Data Roaming and Seamless Technology change. Keywords:Virtual Roaming, Number Continuity, Seamless technology change, Policy Charging and Control, LTE LBS, Steering of Roaming, GTP Hub, MMS Hub,RADIUS Hub, DIAMETER Hub